The Role of Residential HVAC Units in Demand Side Flexibility Considering End-User Comfort - Erdinc, Ozan; Tascikaraoglu, Akin; Eren, Yavuz; Paterakis, Nikolaos G.; Gibescu, Madeleine; Catalao, Joao P. S. (IEEE, 2016)
There are several services such as peak load reduction and frequency regulation that can be provided by exploiting the thermostatically-controllable appliances (TCAs) demand response (DR) potential. To stimulate the adoption of DR strategies, preserving the end-user comfort level is a crucial issue. In this regard, as a novel contribution to the existing literature, this study proposes a DR strategy for residential heating, ventilation and air conditioning (HVAC) units aiming to minimize average end-user comfort violation, while satisfying the requirements of the load serving entity. The proposed approach manipulates the temperature set-point of HVAC thermostats of the enrolled end-users. Besides, a spatio-temporal to obtain weather forecasts is developed.
Keywords: Demand response; direct load control; heating; ventilation and air conditioning (HVAC) units; thermostatically controllable appliances; weather forecasting; THERMOSTATICALLY CONTROLLED LOADS; MODEL; DEVICES; IMPACT; Energy & Fuels; Engineering